Recent divergence in functional traits affects rates of speciation in the Neotropical Velloziaceae (Pandanales) - De Freitas Larocca, Paula; Saldanha Mancio, Jessica; Padilha, Patricia; Mello-Silva, Renato; Alcantara, Suzana (Botanical journal of the Linnean Society, 2022)
Abstract The resurrection plant family Velloziaceae are an iconic element in the Brazilian campos rupestres, where Barbacenia and Vellozia have undergone episodes of explosive species accumulation. Here we focus on the patterns of evolution of growth forms, dry-season physiological strategies and morphofunctional divergence to untangle these radiations. The timings of marked ‘disparification’ (evolution of trait disparity throughout a clade) in both genera were uncoupled from the shifts towards increased diversification rates, with the former accumulating during the Plio-Pleistocene (< 5 Mya). Except for growth forms in Vellozia, the traits analysed display convergent evolution in both genera. Morphofunctional diversity is lower in Barbacenia than in Vellozia, reflecting a young radiation occurring mostly in the southern Espinhaço Province. Growth-form divergence in Vellozia coincided with the Oligocene/Miocene burst in diversification, followed by a slowdown in rate. Moreover, the recent morphofunctional disparification indicates pulses of trait divergence within a mature radiation. Both growth form and divergence in functional traits affect diversification rates in the genera, with the growth forms displaying fastest diversification usually associated with mountain radiations.